Photobiomodulation Therapy After Mesiodens Surgery: Evaluation of Immunological Markers and Three-Dimensional X-Ray Analysis-Placebo-Controlled Study - Sediva, Eliska; Dostalova, Tatjana; Urbanova, Petra; Eliasova, Hana; Podzimek, Stepan; Misova, Eva (Photobiomodulation, photomedicine, and laser surgery, 2022)
Objective: Photobiomodulation therapy (PBMT) applies therapeutic lasers or light-emitting diodes radiation to the surface of the body. From the medical point of view, PBMT systems have been employed for reducing pain, inflammation, and edema, promoting healing of wounds, deeper tissues and nerves, preventing tissue damage, etc. Background data: PBMT or biostimulation has a wide range of applications in maxillofacial surgery. It is known that the therapy effect using three-dimensional (3D) image was not really clear during the healing process. Materials and methods: The treatment group comprised 38 patients, 18 of them were treated with laser radiation (diode laser 808 nm) and 20 patients presented the control group. The surgery plan was monitored using cone beam computed tomography, in particular the number, shape, and size of mesiodens were registered. The effectivity of laser therapy was assessed based on immunological tests-secretory immunoglobulin A (sIgA) and lysozyme levels measured in nonstimulated saliva before and after treatment. Results: For sIgA (both in millimeters and milligrams per liter), the measurements displayed differences between pre- and postsurgery values, the postsurgery values being significantly lower than the presurgery values. In addition, interaction with the laser treatment plan was found, meaning that the laser treatment affected the sIgA levels. The decrease in sIgA levels in the control group was statistically significant. However, there was no significant change in sIgA levels in the laser group. The lysozyme trends appeared to be identical to the sIgA levels, that is, rising in the laser group and decreasing in the control group. The initial values for each group, however, go in the opposite direction. Conclusions: The study has shown that the 3D techniques and technologies in combination with therapeutic laser systems could support not only a treatment plan, but they also directly influence the process of healing and reduce inflammation. The study was carried out under clinical project No. 00064203 (FN MOTOL).
Keywords: rentgenové záření; X-Rays; Immunoglobulin A, Secretory; Inflammation; Lasers, Semiconductor; Low-Level Light Therapy; lidé; zánět; biologické markery; laserová terapie s nízkou intenzitou světla; lasery polovodičové; Muramidase; Biomarkers; imunoglobulin A sekreční; muramidasa; Humans